RELIGIOSITY EFFECT ON FERTILITY STUDY GROUP ON ISLAM - Radhiah, Sitti; Stang, Stang; Arsi, Andi Arsunan (Tadulako University, 2018)
Background & Objective : Modernizationis consideredby someto fail inmaintaining moral valuesand humanity, causing increased tendency for people tobelieve inreligious values are considered able to provide solutions tovarious problems of life, so they are constantly adjusting options and decisions included in determinings ome matters related to fertility.The aim of the research was to investigate the determinants of woman fertility of reproductive couples in Islamic study group in South Palu Distric of Palu City. Material and Method : The reasearch was an observational study with cross sectional study design. The samples were the total population of the women of reproductive couples in Islamic study group of Soth Palu District consisting of 149 people. The method of obtaining the data was interview and the data were analyzed using path analysis. Results: The research indicate that the variable affecting the age of the first marriage is employment (p=0.004); the variables affecting contraception are knowledge (p=0.002) and religiosity (p=0.000); the variable affecting unmet need is religiosity (p=0.019); the variables affecting fertility are knowledge (p=0.014), employment (p=0.006), age of the first marriage (p=0.021), contraception (p=0.008), and unmet need (p=0.002), while income and breastfeeding duration do not significantly affect fertility. Conclusion : The effect on the fertility of the group is the study of Islamic knowledge, employment, age at first marriage, contraception and unmet need